х= 0,75 или х= -0,2
Пошаговое объяснение:
(-4х-3)(3х+0,6)=0
-4х-3=0 или 3х+0,6=0
-4х=3 или 3х= -0,6
х= -3/4 или х= -0,6/3
х= -0,75 или х= -0,2
(-4x-3)(3x+0,6)=0
-4x-3=0 и 3х+0,6=0
-4х=3 3х= - 0,6
Х= - 3/4 х= - 0,6:3
Х= - 0,75 х= - 0,2
ответ : х1= - 0,75 х2= - 0,2
х= 0,75 или х= -0,2
Пошаговое объяснение:
(-4х-3)(3х+0,6)=0
-4х-3=0 или 3х+0,6=0
-4х=3 или 3х= -0,6
х= -3/4 или х= -0,6/3
х= -0,75 или х= -0,2
Пошаговое объяснение:
(-4x-3)(3x+0,6)=0
-4x-3=0 и 3х+0,6=0
-4х=3 3х= - 0,6
Х= - 3/4 х= - 0,6:3
Х= - 0,75 х= - 0,2
ответ : х1= - 0,75 х2= - 0,2